Glycosylation and methylation in the biosynthesis of isoflavonoids in Pueraria lobata - Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2023)
The pathway for forming isoflavonoid skeletal structure is primarily restricted to the Leguminosae family. Subsequent decorations on the compound backbone by tailoring enzymes would change their biological and medicinal properties. Pueraria lobata is a leguminous plant, and as a traditional Chinese medicine its roots have been ascribed a number of pharmacological activities. Glycosylation and methylation are the main modifying processes in isoflavonoid metabolism in P. lobata roots, resulting in the accumulation of unique glycosylated and methylated end isoflavonoid compounds. For instance, daidzein 8-C-glucoside (i.e., puerarin) and puerarin derivatives are produced only by the Pueraria genus. Puerarin has been established as a clinical drug for curing cardiovascular diseases. To better understand the characteristic isoflavonoid metabolism in P. lobata, this review attempts to summarize the research progress made with understanding the main glycosylation and methylation of isoflavonoids in P. lobata and their biosynthetic enzymes.